Recurrent Embolic Strokes of Undetermined Source in a Patient with Extreme Lipoprotein(a) Levels - Bulwa, Zachary; Kim, Audrey; Singh, Karandeep; Kantorovich, Alexander; Suhail, Faten (Frontiers in Neurology, 2016)
Lipoprotein(a) is a plasma lipoprotein and known cardiovascular risk factor most recently implicated in the development of high-risk carotid atherosclerotic plaques without significant carotid stenosis. We present a case of a young African-American female with recurrent embolic strokes of undetermined source. After our thorough investigation we identified the link between a small, irregular plaque in the right internal carotid artery and an extremely elevated plasma level of lipoprotein(a) as the source of her embolic strokes.